Fish catch composition of selected small scale fishing gears used in the Bonny River, Rivers State, Nigeria - Olopade, Olaniyi Alaba; Sinclair, Nkuene Gbenekanu; Dienye, Henry (Journal of Fisheries, 2017)
Fish catch composition of some selected small scale fishing gears (gill net, cast net, beach seine and long line) were investigated in Bonny River, Rivers State, Nigeria from August 2014 to January 2015. A total number of 25 fish species from 18 families were recorded during the study. The Mugilidae with only one species constituted the dominant family while Cichlidae, Lutjanidae, Clupeidae, had three species and Scianidae had two species of fish caught and the remaining families had one species each. Mugil cephalus constituted 28.48% of the total catches followed by C. nigrodigitatus (22.48%). In the dry season M. cephalus forms the major component landings (32.65%), followed by C. nigrodigitatus (26.53%) and S. galilaeus (12.24%) while in the wet season M. cephalus (31.06%), C. nigrodigitatus (18.63%) and T. zillii (11.80%) were the dominant fish species. Cast net was the most efficient fishing gear while gill net was the least efficient. The comparison analysis between the wet and dry seasons using t-test showed no significant difference between dry and wet seasons (t = 0.092, P > 0.05).